Neural Substrates of Visual Spatial Coding and Visual Feedback Control for Hand Movements in Allocentric and Target-Directed Tasks - Thaler, Lore; Goodale, Melvyn A. (Frontiers in Human Neuroscience, 2011)
Neuropsychological evidence suggests that different brain areas may be involved in movements that are directed at visual targets (e.g. pointing or reaching), and movements that are based on allocentric visual information (e.g. drawing or copying). Here we used fMRI to investigate the neural correlates of these two types of movements in healthy volunteers. Subjects (n=14) performed right-hand movements in either a target-directed task (moving a cursor to a target dot) or an allocentric task (moving a cursor to reproduce the distance and direction between two distal target dots) with or without visual feedback about their hand movement. Movements were monitored with an MR compatible touch panel. A whole-brain analysis revealed that movements in allocentric conditions led to an increase in activity in the fundus of the left intraparietal sulcus (IPS), in posterior IPS, in bilateral dorsal premotor cortex (PMd), and in the Lateral Occipital Complex (LOC). Visual feedback in both target-directed and allocentric conditions led to an increase in activity in area MT+, superior parietal occipital cortex (SPOC) and posterior IPS (all bilateral). In addition, we found that visual feedback affected brain activity differently in target-directed as compared to allocentric conditions, in particular in pre-supplementary motor area, PMd, IPS and parieto-occipital cortex. Our results, in combination with previous findings, suggest that the LOC is essential for allocentric visual coding and that SPOC is involved in visual feedback control. The differences in brain activity between target-directed and allocentric visual feedback conditions may be related to behavioral differences in visual feedback control. Our results advance the understanding of the visual coordinate frame used by the LOC. In addition, because of the nature of the allocentric task, our results have relevance for the understanding of neural substrates of magnitude estimation and vector-coding of movements.